Chapter Conclusioni - ROMANO, ANTONELLO (Strumenti per la didattica e la ricerca, 2022)
The Atlas wanted to bring attention to the role of digital platforms as an interface between the space of flows and the space of places by highlighting the digitally-mediated (socio-spatial) effects in the emerging platform society.